1991
DOI: 10.1055/s-2007-1020001
|View full text |Cite
|
Sign up to set email alerts
|

Collagen-presealed or Uncoated Aortic Bifurcation Dacron Prostheses: A 5-Year Clinical Follow-up Study

Abstract: A total of 70 patients undergoing replacement of the aortic bifurcation between October 1983 and June 1985, were studied 5 years postoperatively for graft patency. In 35 cases a collagen-coated knitted Dacron prosthesis (group I) was implanted, while an identical, but uncoated, Dacron graft was used in a second group of 35 patients (group II). Distribution of vascular risk factors were similar in both patient groups. The underlying disease was aortoiliac occlusive disease in 24 patients of group I and in 33 of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Surface modifications involving albumin, 25,26 collagen, [26][27][28] polymers, [29][30][31][32] endothelial cells, 7,33,34 autologous tissue seeding, 35,36 and localized delivery of antithrombotic agents [37][38][39] have not resulted in increased long-term patency rates of such grafts in clinical applications. However, recent research involving the mechanism of thrombosis formation has suggested that NO may be crucial for the prevention of thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…Surface modifications involving albumin, 25,26 collagen, [26][27][28] polymers, [29][30][31][32] endothelial cells, 7,33,34 autologous tissue seeding, 35,36 and localized delivery of antithrombotic agents [37][38][39] have not resulted in increased long-term patency rates of such grafts in clinical applications. However, recent research involving the mechanism of thrombosis formation has suggested that NO may be crucial for the prevention of thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of hemostatic aortic graft material in this case was Hemashield (Boston Scientific), which, although hemostatic, has not been associated with acute intravascular thrombosis. 9,10 The mechanism of this fatal thoracic aortic thrombosis is unclear. Fatal thrombosis has been reported in adult DHCA; the antifibrinolytic, however, was not aprotinin but aminocaproic acid.…”
Section: Position Of the Shoulder For Subclavian Approachmentioning
confidence: 99%
“…9 By contrast, in Jamaica, where transfusion practices are far more conservative, a study of 250 patients documented an infection rate of 2%. 10 Rather than preventing acute sickle problems, transfusion can actually precipitate acute pain 11 and pulmonary complications. 12 We do not suggest that our review is the last word on management or even that the model we outline explains all aspects of sickle cell disease.…”
mentioning
confidence: 99%